1991
DOI: 10.1016/0960-0760(91)90358-c
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro studies on sex steroid binding protein (SBP) regulation in rainbow trout (oncorhynchus mykiss): Influence of sex steroid hormones and of factors linked to growth and metabolism

Abstract: Summary--The respective roles of sex steroids and hormones related to growth and metabolism, on SBP regulation have been studied in rainbow trout. In vivo, oestradiol (E2) supplementation induces a slow but significant increase of plasma SBP concentration. Testosterone or cortisol injections have no effect. In vitro, the steroid binding protein that accumulates in incubation medium of hepatic cell primary cultures has been characterized and found to be similar to blood SBP. Its production is increased by addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…These results are different from those obtained in mammals, where SSBPs are not affected by castration (von Shoultz and Carlstrom, 1989) and androgens seem to play an inhibitory action on SSBP levels in vivo (Toscano et al, 1992;Koritnik and Marschke, 1986;Kottler et al, 1988;). In the only other lower vertebrate studied so far, the trout, androgens do not affect SSBP plasma levels, a result also confirmed by in vitro observations (Foucher et al, 1991). On the contrary, in Rana esculenta testosterone affected EBP binding capacity.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These results are different from those obtained in mammals, where SSBPs are not affected by castration (von Shoultz and Carlstrom, 1989) and androgens seem to play an inhibitory action on SSBP levels in vivo (Toscano et al, 1992;Koritnik and Marschke, 1986;Kottler et al, 1988;). In the only other lower vertebrate studied so far, the trout, androgens do not affect SSBP plasma levels, a result also confirmed by in vitro observations (Foucher et al, 1991). On the contrary, in Rana esculenta testosterone affected EBP binding capacity.…”
Section: Discussionsupporting
confidence: 71%
“…Since SSBP are believed to be mainly synthesized in the liver (Mercier-Bodard et al, 1989), we can hypothesize a testosterone effect through its aromatization to 17β-estradiol. Indeed, estrogens have been reported to increase SSBP in human, heifer and trout (Toscano et al, 1992;Lermite and Terqui, 1991;Foucher et al, 1991), although they have little or not effect in monkeys (Koritnk and Marschke, 1986;Kottler et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Various techniques have been used to culture fish hepatocytes [35,37]. We chose to use the system first developed by Flouriot and Valotaire [38] and modified by Foucher et al [39], in which gentle shaking is used to encourage the hepatocyte to form small aggregates, as a first step towards tissue organization [40]. In our system, the cells are kept for 10 to 12 days (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, we demonstrated that in trout, in vivo, variations of plasma SBP levels coincided with perturbations of the GH/IGF system (Foucher et al 1992) and that in vitro, recombinant tGH (1-1000 ng/ml) maintained and stimulated SBP production by trout hepatocytes in culture (Foucher et al 1991). Also, GH may exert a selective stimulation of rat liver cytosolic E 2 receptor (Lucier et al 1981;Von Schoultz and Carlstr6m 1989).…”
Section: Other Interactionsmentioning
confidence: 76%
“…In our hands, GH either alone or in cotreatment with E 2 (10 -7 -10 -6 M) was found to have a slight inhibitory effect on vitellogenin (Vg) accumulation in trout hepatocyte culture medium (Foucher et al 1991) and no effect on Vg mRNA concentration in cultured hepatocytes (Flouriot and Valotaire, unpublished data). However, in vivo, GH was shown to enhance the stimulatory effect of low E 2 doses (0.56 tg/3 times a week/24 days) on Vg plasma levels in female silver eels (Burzawa-Gerard and Delevall6e-Fortier 1992).…”
Section: Other Interactionsmentioning
confidence: 82%